Low-Dose-Rate Irradiation for 1 Hour Induces Protection Against Lethal Radiation Doses but Does Not Affect Life Span of DBA/2 Mice - Nina Frederike Jeppesen Edin; Čestmír Altaner; Veronika Altanerova; Peter Ebbesen; Erik O. Pettersen (SAGE Publishing, 2016)
Prior findings showed that serum from DBA/2 mice that had been given whole-body irradiation for 1 hour at a low dose rate (LDR) of 30 cGy/h induced protection against radiation in reporter cells by a mechanism depending on transforming growth factor β3 and inducible nitric oxide synthase activity. In the present study, the effect of the 1 hour of LDR irradiation on the response of the preirradiated mice to a subsequent lethal dose and on the life span is examined. These DBA/2 mice were prime irradiated for 1 hour at 30 cGy/h. Two experiments with 9 and 9.5 Gy challenge doses given 6 weeks after priming showed increased survival in primed mice compared to unprimed mice followed up to 225 and 81 days after challenge irradiation, respectively. There was no overall significant difference in life span between primed and unprimed mice when no challenge irradiation was given. The males seemed to have a slight increase in lifespan after priming while the opposite was seen for the females.